Retinal thickness in children with anisohypermetropic amblyopia. Issue 8 (13th February 2015) - Nishi, Tomo; Ueda, Tetsuo; Hasegawa, Taiji; Miyata, Kimie; Ogata, Nahoko
Abstract : Purpose: To determine the thickness of the fovea in eyes of children with anisohypermetropic amblyopia, their fellow eyes and eyes of age-matched controls. Additionally, to assess the effects of optical treatment on the foveal thickness in eyes with anisohypermetropic amblyopia. Materials and methods: Twenty-one patients (6.0±2.3 years, mean±SD) with anisohypermetropic amblyopia and 25 age-matched controls (5.6±1.9 years) were studied. Spectral-domain optical coherence tomography (SD-OCT) was used to obtain OCT images. The foveal thickness and the thickness of the outer nuclear layer (ONL), photoreceptor inner segment (IS) layer and outer segment (OS) layer were measured by the embedded OCT software. Results: The length of the OS was significantly greater in the fellow eyes (48.0±6.6 µm) than in the amblyopic eyes (42.4±4.6 µm, p=0.03). One year after the optical treatment of the anisohypermetropia, the best-corrected visual acuity (BCVA) improved and the length of the OS was significantly increased (p=0.0001). After optical treatment, there was no more significant difference in the OS length between the amblyopic eyes and the fellow eyes (p=0.95). The change of BCVA was significantly correlated with the change of the length of the OS 1 year after the treatment (r=0.52; p=0.0004). Conclusions: Anisohypermetropic amblyopic eyes have qualitative and quantitative differences in the retinal microstructures of the fovea from normal eyes. An increase in the OS length was detected in the amblyopic eyes after the optical treatment. A significant correlation was found between the increased OS length and better BCVA. Trial registration number: The trial registration number of the internal review board of Nara Medical University was 774.